PENGARUH PERSEPSI WAJIB PAJAK ORANG PRIBADI TENTANG KEBERMANFAATAN e-FILING, KEMUDAHAN PENGGUNA e-FILING, DAN KEPUASAN PENGGUNA e-FILING TERHADAP PENGGUNAAN e-FILING SEBAGAI SARANA PELAPORAN PAJAK - Rusmanto -; Ria Widuri (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This research aims to analyze the influence of the perception of individual taxpayers about the usefulness of e-Filing, e-Filing User ease, and e-Filing user satisfaction on the use of e-Filing as a means of tax reporting (Case Study In Individual Personal Tax Payer In Consultant Office Tax HLP Consultant).The population in this study are all individual taxpayer clients in the Fa. HLP Consultant which amounts to 218 taxpayers. Based on the criteria of purposive sampling method, the sample taken is 100 people. Data collection technique is done by questionnaire. Methods of data analysis using multiple linear regression model with statistical analysis techniques used in the form of software SPSS Version 22.00 for windows.The conclusion of this research is t-test result for perception about e-Filing usage with value 0.000 perception about e-Filing user ease with value 0,001 and e-filing user satisfaction with value 0,001 influence to e-filing usage as tax reporting facility. While the F test results of 0.000 <0.05, simultaneously the three variables used in this study significantly influence the use of e-Filing as a means of tax reporting.